What determines whether teachers enhance self-regulated learning? Predicting teachers’ reported promotion of self-regulated learning by teacher beliefs, knowledge, and self-efficacy - Dignath, Charlotte (Frontline Learning Research, 2017)
In this study, the predictive value of three aspects of teacher beliefs for teachers’ promotion of self-regulated learning (SRL) is modelled by means of structural equation modelling: teacher beliefs on (1) instructing SRL, (2) regarding their own self-efficacy towards the promotion of SRL, and (3) teachers’ epistemological beliefs regarding learning. 173 primary school teachers participated in the study. Path analysis revealed that teachers’ beliefs on instructing SRL and self-efficacy beliefs regarding the promotion of SRL were predicting teachers’ promotion of SRL most positively. The results offer new insights into teacher beliefs and how they account for teacher behavior regarding the promotion of SRL. This study is particularly innovative as it is the first study in the field of teachers and SRL to investigate teacher beliefs and teacher self-efficacy as potential determinants of teachers’ promotion of SRL in the classroom. These results can serve to construct a model of teachers’ promotion of SRL as well as provide ideas on how to help teachers supporting SRL. This study is frontline as to my understanding no other research has been published on teachers’ beliefs, in particular self-efficacy beliefs towards promoting SRL, and how these are related to teachers’ promotion of SRL. Most research on teachers and SRL has so far focused on training teachers, but no model of teachers’ professional competence in this area exists yet.